Penta‐Twinned Copper Nanorods: Facile Synthesis via Seed‐Mediated Growth and Their Tunable Plasmonic Properties. (7th January 2016) - Luo, Ming; Ruditskiy, Aleksey; Peng, Hsin‐Chieh; Tao, Jing; Figueroa‐Cosme, Legna; He, Zhike; Xia, Younan
Abstract : The use of seed‐mediated growth as a versatile approach to the synthesis of penta‐twinned Cu nanorods with uniform diameters and controllable aspect ratios is reported. The success of this approach relies on our recent synthesis of uniform Pd decahedra, with sizes in the range of 6–20 nm. The Pd decahedral seeds can direct the heterogeneous nucleation and growth of Cu along the fivefold axis to produce nanorods with uniform diameters defined by the lateral dimension of the original seeds. Due to a large mismatch in the lattice constants between Cu and Pd (7.1%), the deposited Cu is forced to grow along one side of the Pd decahedral seed, generating a nanorod with an asymmetric distribution of Cu, with the Pd seed situated at one of the two ends. According to extinction spectra, the as‐obtained Cu nanorods can be stored in water under the ambient conditions for at least six months without noticeable degradation. This excellent stability allows us to systematically investigate the size‐dependent surface plasmon resonance properties of the penta‐twinned Cu nanorods. With the nanorod transverse modes positioned at 560 nm, the longitudinal modes can be readily tuned from the visible to the near‐infrared region by controlling the aspect ratio. Abstract : Pd decahedra are used as seeds to direct the nucleation and growth of Cu along the fivefold axis to produce penta‐twinned Cu nanorods with uniform diameters and controllable aspect ratios. The Cu atoms only grow along one side of the decahedral seed, generating a Cu nanorod with the Pd seed at one of the two ends.